"Exchanging Glances": The Inherent Tensions in Rouch's Opus as a Metonymy for the Evolving Prism in French Ethnology - (:unkn) unknown (My University, 2019)
Jean Rouch made important, innovative ethnographic films in West Africa from the late 1940s to the 1970s. There is an evident contrast – in subject and style – between his films about young Africans in the years prior to national independences and the more traditional ethnographic films, in the wake of Griaule, largely focused on the “primitive” and on the “profound Truth” assumed to reside in the Dogon cosmogony. This dualism, which reflects the evolution underway in French ethnography, is a source of tension in Rouch’s corpus of film. In the footsteps of Leiris and Balandier, post-War French ethnography was, at that time, apprehending the rapid changes that Africa was experiencing and was attempting to reconfigure its own theoretical foundations. Rouch may have seemed to be at odds with this new paradigm when filming the Dogon, but at the same time he made films which gave voice and personal identity to their protagonists, foreseeing novel forms of intercultural reflections, akin to the concept of “regards croisés” that certain post-Modern analysts would later prone. In the films about societal shifts in Africa, Rouch mixed as it suited him fiction with the most vital subjects: de-colonialization, modernization, politics, the sociology of population migrations from rural to urban. The watershed work of Balandier, his Sociologie des Brazzavilles noires in particular, and those of Rouch, with les Maîtres fous, Moi, un noir and Jaguar, echoed each other, offering a dynamic approach to African culture. However, the tangible dichotomy in Rouch’s work, with respect to subjects traditional or modern, is not a quirk but rather a trademark reflecting Rouch’s unique itinerary, woven through a transformational period in French ethnology, representing a source of tension within his works, begging to be further explored and contextualized.
Keywords: African Research